Factorisable monoid of generalized hypersubstitutions of typeT = (n) - A. Boonmee (2018)
© 2016, Univerzita Komenskeho. All rights reserved. A generalized hypersubstitution of type T maps any operation symbols to the set of all terms. The extensions of generalized hypersubstitutions are map-pings on the set of all terms. The set of all such generalized hypersubstitutions forms a monoid. In this paper, we determine the set of all unit-regular elements of this monoid of typeT = (n). We also conclude a submonoid of the monoid of all generalized hypersubstitutions of type T = (n) which is factorisable.